(untitled) (Journal of Asian Development Studies, 2025)
The present study examines educational materials and curricula, particularly textbooks and teaching practices, as actors that either reinforce or resist dominant ideological constructs. This research employs Critical Discourse Analysis (CDA) to gain insight into how the language, content, and form of educational resources either inhibit or legitimise ideologies of nationalism, gender roles, race, and capitalism, among others. An analysis of a wide range of textbooks and teaching practices across primary, secondary, and tertiary educational levels reveals the subtle but powerful ways education influences students’ worldviews and beliefs about the society around them. It further suggests that curricula have the potential to disrupt hegemonic ideologies by introducing alternative subject positions, fostering critical thinking, and enabling empowerment. This research contributes to the burgeoning CDA literature by emphasising the ideological thrust of educational discourse and its implications for socialisation, identity formation, and cultural reproduction. The study concludes that curricula and teaching materials must undergo critical review and redesign to foster a more democratic and reflective educational environment.